2017
DOI: 10.1186/s12872-017-0690-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluid upstream shear stress of rabbit aortic stenosis inhibits neointimal hyperplasia by promoting endothelization after balloon injury

Abstract: BackgroundAtherosclerosis is associated with disturbed blood flow characterized by low and oscillatory shear stress (SS), however, few study directly links SS to neointimal hyperplasia in animal model. This study was focused on the effects of changed SS upon the neointimal hyperplasia which responded to balloon injury in a novel rabbit model with partially-constricted abdominal aorta.MethodsWe established a rabbit model subjected to partial abdominal aortic constriction with a cylinder-shaped cannula as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…Resveratrol restrains vascular SMC overgrowth and enhances re‐endothelialization, thus greatly reducing the risk of thrombosis (Yurdagul et al, ). This is consisitent with another study showing that upstream shear stress is important for facilitating re‐endothelialization to avoid neointimal hyperplasia (Liu et al, ). Further studies may focus on the synergistic effect of resveratrol and laminar shear stress in resisting age‐related cardiovascular events.…”
Section: Molecular Basis Of Resveratrol Actionsupporting
confidence: 81%
“…Resveratrol restrains vascular SMC overgrowth and enhances re‐endothelialization, thus greatly reducing the risk of thrombosis (Yurdagul et al, ). This is consisitent with another study showing that upstream shear stress is important for facilitating re‐endothelialization to avoid neointimal hyperplasia (Liu et al, ). Further studies may focus on the synergistic effect of resveratrol and laminar shear stress in resisting age‐related cardiovascular events.…”
Section: Molecular Basis Of Resveratrol Actionsupporting
confidence: 81%
“…Finally, a significant NIH developed at the angioplasty site. In the study by Liu et al, 20 an arterial stenosis occurred upstream rather than downstream of the angioplasty site. At the same time, blood flow and shear stress decreased.…”
Section: Discussionmentioning
confidence: 94%
“…19 Spiguel et al 6 found that low shear stress could enhance NIH caused by balloon injury. However, Liu et al 20 found that the combination of low SS and balloon injury did not result in more significant NIH than balloon injury alone. In the study by Spiguel et al, 6 arterial stenosis occurred downstream of the angioplasty site.…”
Section: Discussionmentioning
confidence: 97%